2010
DOI: 10.2298/aci1003059a
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-assisted reversal of Hartmann's procedure

Abstract: laparoscopic-assisted reversal of Hartmann's procedure promotes faster rehabilitation, its results are not worse than after open approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
7
1
Order By: Relevance
“…In this study, the mean total theatre time of patients in the laparoscopic group was 34 min longer than that of patients in the open group. This result differs from most previous studies, which have reported a shorter mean ‘operative time’ in the laparoscopic group compared with the open group; only Svenningsen et al . reported a longer ‘knife time’ in their laparoscopic group.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this study, the mean total theatre time of patients in the laparoscopic group was 34 min longer than that of patients in the open group. This result differs from most previous studies, which have reported a shorter mean ‘operative time’ in the laparoscopic group compared with the open group; only Svenningsen et al . reported a longer ‘knife time’ in their laparoscopic group.…”
Section: Discussioncontrasting
confidence: 99%
“…published a systematic review and meta‐analysis of eight retrospective studies comparing laparoscopic with open reversal of Hartmann's procedure. Since this review, five further retrospective studies and one large multicentre study using prospectively collected data extracted from the American College of Surgeons National Surgical Quality Improvement Program database have also been published. These studies have consistently supported the hypothesis that laparoscopic reversal of Hartmann's procedure is associated with fewer post‐operative complications, a lower mortality rate and a shorter length of hospital stay compared with open reversal of Hartmann's procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Full texts with relative bibliographies were thus appraised, and a total of 26 studies were eventually deemed suitable for inclusion and data extraction. [2, 11, 17–40] The selection process is given in Fig. 1, while Table 1 describes the general characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Median postoperative pain score was significantly lower in LHR group (range 1–4.75 in OHR; 0–3 in LHR). Time to flatus ranged from 4 to 9 and 2 to 13 days in OHR and LHR group, respectively, and length of hospital stay elicited statistical significance in LHR group ( P = .018) with numerous studies reporting similar results [24–27] …”
Section: Discussionmentioning
confidence: 83%
“…Time to flatus ranged from 4 to 9 and 2 to 13 days in OHR and LHR group, respectively, and length of hospital stay elicited statistical significance in LHR group (P = .018) with numerous studies reporting similar results. [24][25][26][27] There is no consensus on the proper method of gaining pneumoperitoneum. Our first step was takedown of the colostomy and adhesiolysis around the stoma site similar to the first LHR described by Gorey et al in 1993.…”
Section: Discussionmentioning
confidence: 99%